Effects of integrating a brain-based teaching approach with GeoGebra on problem-solving abilities - Siti Seri Kartini Mohd Yatim; Salmiza Saleh; Siti Ainor Mohd Yatim; Hutkemri Zulnaidi (International Journal of Evaluation and Research in Education (IJERE), 2022)
B-Geo Module is a module that has been developed using the brain-based teaching approach (BBTA) integrated with GeoGebra Software (B-Geo Module) is expected to help students’ problem-solving abilities of the topic of Differentiation. The BBTA is a strategy that uses brain-based learning techniques. It was created to be consistent with the individual brain's tendencies and ideal functions in order to ensure that pupils can learn efficiently. Therefore, the proposed of this study is to explore the possible effects of the B-Geo Module on problem-solving abilities for the Topic of Differentiation. A quasi-design of pre-test and post-test experiments was utilized in this study, which included 118 form 4 pupils from rural secondary schools. For school selection, the researchers employed cluster sampling approaches, and for sample selection, they used an intact group. The schools were separated into two groups: experimental and control. The experimental group used the B-Geo Module, while the control group used traditional ICT modules. The instrument used was the Problem-Solving Test of Differentiation. The results of the data analysis showed the effectiveness of the B-Geo Module in the problem-solving abilities in the topic of Differentiation among rural secondary school pupils. The multimedia such as GeoGebra can be the tools for BBTA to facilitate Additional Mathematics teachers in secondary schools to help students solve problem and improved their learning in the topic of Differentiation.